Initiative ,enterprise & economic choices in India - Agarwal, Vinod K. (New Delhi, 1975)
Mr. Vinod K. Agarwal's study of entrepreneurship is an important contribution to our understanding of economic processes in India. The reason this study is superior to many others is that Mr. Agarwal skillfully combines economic theories and problems at the larger level with his own sensitive feeling for the cultural, historical and social circumstances out of which entrepreneurship in India has emerged. The result has been to move the discussion of entrepreneurship from the level of abstract and arbitrary formulations to the level of concrete historical and cultural examples of economic processes.
Keywords: Entrepreneur